2017
DOI: 10.1111/jora.12318
|View full text |Cite
|
Sign up to set email alerts
|

Using an Acculturation‐Stress‐Resilience Framework to Explore Latent Profiles of Latina/o Language Brokers

Abstract: With survey data from 243 Latina/o early adolescent language brokers, latent profile analyses were conducted to identify different types (i.e., profiles) of brokers. Profiles were based on how often Latina/o early adolescents brokered for family members, as well as their levels of family-based acculturation stress, negative brokering beliefs, parentification, and positive brokering beliefs. Three brokering profiles emerged: (1) infrequent-ambivalents, (2) occasional-moderates, and (3) parentified-endorsers. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
(128 reference statements)
3
24
0
Order By: Relevance
“…There is also evidence that the configuration of language brokering experiences matters in predicting positive or negative consequences on adolescent mental health. Kam et al (2017) identified three types of Latino adolescent language brokers: infrequent–ambivalents (least likely to language broker, with low positive and negative feelings about language brokering and low levels of parentification, which refers to parents relying on their children), occasional–moderates (moderate language brokering with moderate positive and low negative feelings about language brokering and low levels of parentification), and parentified–endorsers (most likely to language broker, with high positive and low negative feelings about language brokering and high levels of parentification). Kam et al found that occasional–moderates showed the most positive outcomes, as this profile membership did not predict discrimination, depressive symptoms, or risky behaviors.…”
Section: Parental Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that the configuration of language brokering experiences matters in predicting positive or negative consequences on adolescent mental health. Kam et al (2017) identified three types of Latino adolescent language brokers: infrequent–ambivalents (least likely to language broker, with low positive and negative feelings about language brokering and low levels of parentification, which refers to parents relying on their children), occasional–moderates (moderate language brokering with moderate positive and low negative feelings about language brokering and low levels of parentification), and parentified–endorsers (most likely to language broker, with high positive and low negative feelings about language brokering and high levels of parentification). Kam et al found that occasional–moderates showed the most positive outcomes, as this profile membership did not predict discrimination, depressive symptoms, or risky behaviors.…”
Section: Parental Socializationmentioning
confidence: 99%
“…Kam et al found that occasional–moderates showed the most positive outcomes, as this profile membership did not predict discrimination, depressive symptoms, or risky behaviors. Parentified–endorsers were most at risk for discrimination and depressive symptoms, while infrequent–ambivalents were less engaged in risky behaviors (Kam et al 2017). These results suggest that assessing the context in which language brokering occurs may be more important than simply assessing the feelings surrounding it to understand its protective and risk functions in children of immigrants.…”
Section: Parental Socializationmentioning
confidence: 99%
“…As the multifaceted nature of language brokering is being uncovered, researchers have found that how children perceive their brokering experiences works jointly with objective aspects of brokering in determining the role this activity plays in their lives (Kam & Lazarevic, 2014b; Kim, Hou, Shen, et al, 2017). More recently, scholars have begun to realize the need to consider language brokering together with the contexts in which the brokers are embedded, given that language brokering is a highly contextualized activity (Kam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, given the multidimensionality of the language brokering experience, it makes sense that there would be different configurations involving varying levels of frequency and centrality, as well as positive and negative subjective experiences. A recent study using a sample of Latino adolescents, for example, identified three broker profiles based on the multifaceted language brokering experiences and family contexts (i.e., brokering frequency, levels of family-based acculturation stress, negative brokering beliefs, and positive brokering beliefs, (Kam, Marcoulides, & Merolla, 2017). They found that the profile characterized by high scores on all indicators was associated with more negative socio-emotional outcomes; the profile characterized by low scores on all indicators, instead, was associated with more positive behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation